The therapeutic effects of ADSCs on photoaging of skin induced by UVB irradiation: ADSCs’ impact on UVB-induced Skin photoaging - Wang, Jing; Zhou, Xiaochen; Cao, Di; Meng, Ying; Wang, Yingchun; Yang, Debin (Cellular and Molecular Biology, 2024)
Skin photoaging affects appearance and is associated with a variety of skin diseases, even skin cancer. Therefore, the prevention and treatment of skin photoaging is very important. However, there is a lack of effective evaluation methods, so it is an urgent problem to explore a comprehensive, non-invasive and in vivo evaluation method. Adipose-derived mesenchymal stem cells (ADSCs) are widely used to improve skin conditions as easier to obtain and positive effects. Recently, as the development of ultrasound technology, skin ultrasound has been widely used. Changes in skin layer and structure can be observed by high-frequency ultrasound (HFUS). In addition, Shear wave elastography (SWE) technology can be used to monitor the change of skin hardness. However, it is necessary to further explore the ultrasound parameters in interpreting histological changes. We simulate the progression and treatment process of human skin photoaging by using UVB-induced nude mice skin photoaging model and ADSCs injection. The analysis of the degree and therapeutic effect of skin photoaging was conducted by HFUS, SWE and to verify with histopathology. Our study aims to clarify the value of HFUS combined SWE techniques in evaluating the degree and therapeutic efficacy of skin photoaging, which provides theoretical basis for diagnosis and treatment evaluation systems.